Why is the Tc So High in Fe-Based Pnictide and Chalcogenide Superconductors?. Issue 1684 (18th September 2014) - Haugan, T.; Matsumoto, K.; Puig, T.; Wu, J.; Lv, Bing; Deng, Liangzi; Wu, Zheng; Wei, Fengyan; Zhao, Kui; Meen, James K.; Xue, Yu-Yi; Wang, Li-Li; et al.
ABSTRACT Recently, the detection of non-bulk superconductivity with unexpectedly high onset-Tcs up to 49 K in Pr-doped CaFe2As2 [(Ca, Pr)122] single crystals and the report of a Tc up to 65 K in one-unit-cell (1UC) FeSe epi-films, offer an unusual opportunity to seek an answer to the question posed in the title. Through systematic compositional, structural, resistive, and magnetic investigations on (Ca, Pr)122 single crystals, we have observed a doping-level-independent Tc, the simultaneous appearance of superparamagnetism and superconductivity, large magnetic anisotropy, and the existence of mesoscopic-2D structures in these crystals, thus providing clear evidence consistent with the proposed interface-enhanced Tc in these naturally occurring rareearth-doped Fe-based superconductors, (Ca, R)122. Similar resistive and magnetic measurements were also made on the 3â€"4UC FeSe ultrathin epi-films. We have detected weak links in the Meissner state below 20 K, weakly coupled small superconducting patches between 20â€"45 K, and collective excitations of spin and/or superconducting nature between 45â€"80 K. The unusual frequency dependences of the diamagnetic moment observed in the films in different temperature ranges will be presented and their implications discussed.